2009
DOI: 10.1160/th08-12-0830
|View full text |Cite
|
Sign up to set email alerts
|

The VEGF-induced transcriptional response comprises gene clusters at the crossroad of angiogenesis and inflammation

Abstract: VEGF-A is the major trigger of vasculogenesis and physiologic angiogenesis. We have investigated to which extent the gene repertoire induced by VEGF-A in endothelial cells is distinct from that of other growth factors and inflammatory cytokines. Genes upregulated in human umbilical vein endothelial cells treated with VEGF, EGF or IL-1 were compared by microarray analysis and clusters characteristic for individual or combinations of inducers were defined. VEGF-A upregulated in comparison to EGF a five-fold larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 46 publications
8
104
2
1
Order By: Relevance
“…The RNA-seq data was validated by qRT-PCR and was generally concordant with previously reported microarray gene expression profiling data for HUVECs stimulated with VEGFA for 0 and 1 h (Supplemental Fig. 11B,C; Schweighofer et al 2009) and ENCODE HUVEC RNAseq data (Supplemental Fig. 12).…”
Section: Temporal Clustering Of H3k27ac Variation Defined Groups Of Csupporting
confidence: 85%
See 1 more Smart Citation
“…The RNA-seq data was validated by qRT-PCR and was generally concordant with previously reported microarray gene expression profiling data for HUVECs stimulated with VEGFA for 0 and 1 h (Supplemental Fig. 11B,C; Schweighofer et al 2009) and ENCODE HUVEC RNAseq data (Supplemental Fig. 12).…”
Section: Temporal Clustering Of H3k27ac Variation Defined Groups Of Csupporting
confidence: 85%
“…A central regulator of blood vessel growth is vascular endothelial growth factor A. In response to VEGFA signaling, endothelial cells dramatically change their phenotype and gene expression profile (Schweighofer et al 2009). Intracellular signaling downstream from VEGFA has been studied in depth, but relatively less is known about the transcriptional regulatory elements that respond to VEGFA signaling.…”
mentioning
confidence: 99%
“…S8). HLX, a homeobox transcription factor, expression of which is induced by VEGF in vitro (Schweighofer et al, 2009), has been implicated in controlling angiogenic sprouting of human cells in vitro (Prahst et al, 2014;Testori et al, 2011), and in ISV formation in zebrafish (Herbert et al, 2012), as well as yolk sac vascular remodeling in the mouse (Prahst et al, 2014). Further analysis of our ChIP-seq data revealed that the majority of ERG/VEGF-regulated genes (25 of 44) had an ERG ChIP-seq peak within 10 kb of the TSS, and ERG binding was conserved in cow for 16 of these genes (Fig.…”
Section: Erg Regulates a Network Of Constitutive And Vegf-inducible Gmentioning
confidence: 99%
“…And several studies have demonstrated that VEGF induces the upregulation of several kinds of angiogenesis and inflammation factors. 39,40 In our study, Sema3A only inhibited the VEGF 165 induced JNK and p38MAPK phosphorylation partially, but not all of the upregulated signal pathways induced by all of the factors, thus, the phosphorylation of JNK and p38MAPK are only partially inhibited. Besides the behavior study of the RPE cells, we also detected the expression pattern of the two crucial receptors, VEGFR2 and Nrp1, which are important in the function of VEGF 165.…”
Section: Discussionmentioning
confidence: 46%